Safety and anterior chamber structure of evolution implantable Collamer lens implantation with short white-to-white corneal diameters - Chen, Xun; Chen, Fang; Wang, Xuanqi; Xu, Yilin; Cheng, Mingrui; Han, Tian; Wang, Xiaoying; Zhou, Xingtao (Frontiers in Medicine, 2022)
Introduction To evaluate the safety and anterior chamber structure of implantation of the Evolution (EVO) implantable Collamer lens (EVO-ICL) in patients with short white-to-white (WTW) corneal diameters. Materials and methods The study population was divided into two groups: the experimental group (34 eyes of 34 patients) with WTW corneal diameters of ≤10.6 mm and the control group (59 eyes of 59 patients) with WTW corneal diameters of >10.6 mm. The outcome measures included uncorrected distance visual acuity, corrected distance visual acuity, refractive power, intraocular pressure (IOP), anterior chamber angle, depth, volume, and vault. Results The safety indices of the experimental and control groups were 1.17 ± 0.30 and 1.12 ± 0.14, respectively (P > 0.05); the effectiveness indices were 1.16 ± 0.31 and 1.07 ± 0.17, respectively (P > 0.05). The simulation curves of the expected and actual corrections in the experimental and control groups were y = 0.9876x – 0.0927 and y = 0.9799x + 0.0343, respectively. There were no significant differences between the IOPs and anterior chamber structures of the two groups (P > 0.05). The average vaults of the experimental and control groups were 395.76 ± 155.32 and 389.49 ± 135.01 μm, respectively (P > 0.05). Conclusion EVO-ICL implantation in patients with short WTW corneal diameters (≤ 10.6 mm) was determined to be a safe, effective, and predictable method for correcting myopia. The changes in the anterior chamber structure were still within normal limits after the surgery, the IOP remained stable, and the ideal vault was achieved after the surgery.